A Holistic Examination of How Professional Learning and Curriculum Relate to Ambitious and Culturally Relevant Instruction and Student Engagement - Laura M. Desimone; Nick Bell; Arielle Lentz; Kirsten L. Hill; Latrice Marianno (AERA Open)
To shape professional learning (PL) and curriculum interventions for successfully transforming instruction, we need to better understand how multiple aspects of the system work. Applying structural equation modeling with a sample of 437 teachers in 153 middle and high schools in 11 districts serving 50% or more Black or Latinx students, we found that teachers are significantly more likely to use ambitious and culturally responsive (CR) instruction in the classroom and that student engagement increases when PL and curriculum adoption are (1) targeted toward ambitious and CR instruction, (2) provide clear, specific directions to teachers, (3) are aligned with each other, (4) are supported by teachers, and (5) are accompanied by incentives. PL worked through fostering stronger beliefs in and confidence using CR instruction. The curriculum and PL had both independent and interactive effects on bolstering the use of ambitious and CR instruction.